2008
DOI: 10.1073/pnas.0803277105
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric subunit stoichiometry of the human voltage-dependent proton channel Hv1

Abstract: In voltage-gated Na ؉ , K ؉ , and Ca 2؉ channels, four voltage-sensor domains operate on a central pore domain in response to membrane voltage. In contrast, the voltage-gated proton channel (Hv) contains only a voltage-sensor domain, lacking a separate pore domain. The subunit stoichiometry and organization of Hv has been unknown. Here, we show that human Hv1 forms a dimer in the membrane and define regions that are close to the dimer interface by using cysteine cross-linking. Two dimeric interfaces appear to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
274
3
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(292 citation statements)
references
References 23 publications
12
274
3
3
Order By: Relevance
“…Thus, rigid structure of the linker region enables to mediate the stability of the coiled-coil to the transmembrane domain, and to mediate the cooperative gating within the dimer. Considering the mechanical interaction between two channel subunits, a certain level of physical intersubunit contact between transmembrane regions within a dimer has been reported 9,17 . These make it plausible that two transmembrane regions in close proximity in a dimer physically interact with one another, and the coiled-coil domain facilitates the close positioning of the two transmembrane regions (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, rigid structure of the linker region enables to mediate the stability of the coiled-coil to the transmembrane domain, and to mediate the cooperative gating within the dimer. Considering the mechanical interaction between two channel subunits, a certain level of physical intersubunit contact between transmembrane regions within a dimer has been reported 9,17 . These make it plausible that two transmembrane regions in close proximity in a dimer physically interact with one another, and the coiled-coil domain facilitates the close positioning of the two transmembrane regions (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the cytoplasmic end of S4 helix is close to each other within a dimer, where Cys introduced into the position of Thr222 in hHv1/VSOP make a disulfide bond between two monomers 9 . To examine whether this spatial proximity was disarranged by the GGG mutation, we performed crosslinking experiments by oxidation with the T218C mHv1/VSOP mutants that corresponds toT222C in hHv1/VSOP.…”
Section: Coiled-coil Assembly Domain Of Mhv1/vsop and Its Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Multiple functions were proposed for proton channels, but these remained speculative until the cloning of the Hv1 protein by two separate laboratories (Ramsey et al, 2006;Sasaki et al, 2006) and the generation of Hv1 knockout mice offered the possibility to test the physiological role of proton channels. Structure-function studies revealed that Hv1 channels are dimers that gate cooperatively (Gonzalez et al, 2010;Musset et al, 2010;Tombola et al, 2010), with each monomer containing a separate conduction pathway and voltage sensor (Koch et al, 2008;Lee et al, 2008;Tombola et al, 2008). Hv1 channels are perfectly selective for protons and are activated by depolarizing voltages and by intracellular acidification, a combination that ensures that the channels only open in conditions that favor proton extrusion from cells.…”
mentioning
confidence: 99%